EKSISTENSI DAN PENGATURAN KESATUAN MASYARAKAT HUKUM ADAT SEBAGAI SUBYEK HUKUM TATANEGARA - Johan Erwin Isharyanto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
In the era of independence, guided democracy, the new order, until the era ofgovernance reform in Indonesia tended to override the importance of diversity.Power consolidation tends to deny the existence of customary law community unitsand is usually accompanied by etatism tendencies. This article describes how theexistence and regulation of customary law community units as subjects ofConstitutional Law. The conclusion obtained is that the existence and regulation ofcustomary law community units as subjects of constitutional law in the legal systemof the Republic of Indonesia constitution is guaranteed and recognized based on theprovisions of Article 28 B paragraph (2) article and 28 I paragraph (3) of the 1945Constitution, as well as in Article 6 UU no. 39 of 1999 concerning human rights